Analisis Perbedaan Pendapatan Pedagang Perempuan Pasca Revitalisasi Pasar Seni Klungkung - I Kadek David Sandi Jaya; Ni Made Tisnawati (Lembaga Pengembangan Kinerja Dosen, 2026)
After the revitalization of Pasar Seni Klungkung, several traders particularly female traders experienced a decline in income due to changes in kiosk layout and unstable consumer traffic. Buyers needed time to adjust to the new market arrangement, resulting in lower transaction activity compared to the period before revitalization. This study aims to analyze the differences in income of female traders before and after the revitalization and to identify the factors influencing these changes. The research employs a quantitative approach with data collected through questionnaires and in-depth interviews with market management. Data analysis was conducted using the Wilcoxon test to determine significant changes in income. The results indicate a clear difference in the income of female traders before and after the revitalization, with post-revitalization income tending to decrease. These findings suggest that the post-revitalization adaptation period affects traders’ economic stability and highlights the need for market management strategies that are more responsive to consumer visitation patterns.